Konstruksi Islam sebagai Simbol Identitas melalui Representasi Perempuan Muslim pada Novel Religi - Husnan Nurjuman; Uliviana Restu; Bayu Teja Kususma (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2018)
This paper describes the construction of the practice of Islam as a symbol of group identity in the midst of the reality of society through the representation of Muslim women in the Queen's Religion prostrate novel. This research with a qualitative approach to semiotic analysis from Roland Barthes describes the text with denotative, connotative and mythical systematics. The novel Ratu yang Bersujud which prostrates presents the Islamic concept of Muslim women in the form of protection and breeding for women, the primacy of the role of women in the household, women as male partners and equality of men and women. Representation of the concept of muslim women is part of Islamic construction as a group identity. The construction of reality as a result of the interaction between the writer and the reality of Islamic thought, the reality of women's progress, the reality of the negative stigma of western civilization towards Islam, and the reality of symbolic trends in religious life, which is then disignified in novel texts, and internalized by society. The results of this study become an illustration of the reality of trends in society that make the understanding of Islam about the position of women as representations of identity, through cultural products, in the form of religious novels. The findings and analysis can be an illustration of the process of intervention in social change, including interventions that are da'wah framed. Propagators can use cultural products as a medium or means to internalize various thoughts in Islam into a reality constructed in the community.Tulisan ini menggambarkan konstruksi pengamalan Islam sebagai simbol identitas kelompok  di tengah realitas masyarakat  melalui representasi perempuan muslim pada novel religi Ratu yang Bersujud. Penelitian dengan pendekatan kualitatif analisis semiotika dari Roland Barthes ini menguraikan teks dangan sistematika  denotatif, konotatif dan mitos. Novel Ratu yang Bersujud yang bersujud menghadirkan konsep Islam tentang perempuan muslim berupa perlindungan dan pemuliaan bagi perempuan, keutamaan peran perempuan dalam rumah tangga, perempuan sebagai mitra laki-laki dan  kesetaraan laki-laki dan perempuan. Representasi konsep perempuan muslim merupakan bagian dari konstruksi Islam sebagai identitas kelompok. Konstruksi realitas sebagai hasil interaksi antara penulis dengan realitas pemikiran Islam, realitas kemajuan perempuan, realitas stigma negatif peradaban barat terhadap Islam, serta realitas tren simbolik kehidupan beragama, yang kemudian disignifikasi dalam teks-teks novel, dan diinternalisasi oleh masyarakat. Hasil penelitian ini menjadi gambaran tentang realitas tren di masyarakat yang menjadikan paham agama Islam tentang posisi perempuan sebagai representasi identitas, melalui produk budaya, berupa novel religi. Hasil temuan dan analisis ini dapat menjadi gambaran bagi proses intervensi dalam perubahan sosial, termasuk dalam  intervensi yang berbingkai dakwah. Para pelaku dakwah dapat menggunakan produk budaya sebagai  media atau sarana dalam menginternalisasikan berbagai pemikiran dalam Islam menjadi realitas yang dikonstruksi di tengah masyarakat.